TREN BELANJA ONLINE PADA SOCIAL COMMERCE - Eri Yanti Nasution; Tika Indria (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The growth of social media continues to increase along with the development of information technology. Social media users have interactions via the internet. The social interactions also for business interactions between sellers and consumers. Social media like Facebook, Instagram and Tiktok are used by sellers to offer their products. This research is a descriptive research that aims to explain the trend of social commerce in generation Z. method in this research is descriptive, describing the respondents' answers with graphs that have been obtained through distributing questionnaires to 114 respondents. The results of this study indicate that social commerce is one of the media that Generation Z uses to shop online. Social media was online shopping, because consumers will get a lot of information about products from reviews and rankings of the product based on previous consumer ratings before making a purchase.